Strategic governance and risk management: Unlocking higher stock returns - Rahyuda, Henny; Purbawangsa, Ida Bagus Anom (Edelweiss Applied Science and Technology, 2025)
This study investigates the role of corporate governance in the relationship between financial performance and stock returns, while also exploring the mediating role of business risk in shaping financial outcomes. The analysis uses data from 62 manufacturing companies listed on the Indonesian Stock Exchange from 2021 to 2024, comprising 248 data points. Structural Equation Modeling (SEM) was employed using WARP PLS for the analysis. The findings reveal that business risk significantly mediates the relationship between internal factors, financial performance, and stock returns. Furthermore, financial performance plays a critical mediating role, with significant path coefficients highlighting its influence on internal factors, external factors, and business risk. In contrast, corporate governance was found to have no significant impact on the relationship between financial performance and stock returns. These findings can provide valuable insights for the Financial Services Authority in formulating regulations to protect investors. They can serve as a reference for assessing the impacts of the COVID-19 pandemic on the manufacturing industry, aiding in strategic recovery efforts. This study offers a novel dual-mediation framework that integrates business risk and financial performance in assessing the impact of internal and external factors on stock returns within the Indonesian manufacturing sector during the post-COVID era. Unlike prior research, it reveals the non-significant role of corporate governance in moderating financial outcomes, challenging established theories. Furthermore, the study provides a methodological advancement by utilizing WARP PLS to uncover complex, non-linear relationships. It delivers context-specific insights crucial for policymakers and investors in emerging markets.